Rare Presentation of Wilson Disease in an 11-year-old Sudanese Girl - Dafallah, Mumen Abdalazim; Habour, Elsanosi; Ragab, Esraa Ahmed; Shouk, Zahraa Mamoun; Hamad, Fawzeia; Ahmed, Musaab; Ahmed, Mohamed H. (Sudan Journal of Medical Sciences, 2021)
Background: Wilson disease is an inherited disorder in which excessive amount of copper accumulates in various tissues of the body. Clinical features related to copper deposition in the liver may appear in the first and second decades followed by neurologic and psychiatric thereafter; however, many patients have a combination of these symptoms. Case: We report a case of 11 year-old girl, admitted to Wad Medani Pediatric Teaching Hospital with generalized body swellings for four days. Initial investigations showed proteinuria and hypoalbuminemia, thought to be due to nephrotic syndrome. Days later, patient developed jaundice and neuropsychiatric manifestations. A slit lamb examination confirmed the presence of Kayser–Fleischer ring (KF ring) and she scored high in the scoring system for the diagnosis of Wilson disease. Dpenicillamine treatment therapy was started and unfortunately the patient’s clinical condition deteriorated gradually, and eventually went into deep coma and died. Wilson disease mainly affects the liver, but the initial presentation was completely compatible with nephrotic syndrome. Conclusion: Diagnosis of Wilson disease should be suspected in a child presenting with generalized body swellings even in the absence of clinical evidence of hepatic and/or neuropsychiatric involvements.